Electron Injection for Direct Acceleration by A Gaussian Laser Field Under the Influence of Azimuth Magnetic Field - Singh, Ravindra; ., Sandeep; Kaur, Jaspreet (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
Electron injection for direct acceleration by a circularly polarized Gaussian laser field under the influence of azimuth magnetic field is studied. The electron energy gain, \(γ\) versus electron's injection angle \(δ\) at different values laser intensity parameters and laser spot size shows the energy enhancement on increasing the parameters. For a small change in angle of injection then there appears a significant change in electron energy gain also for the variation of energy gain and magnetic field energy gain increases when value of \(δ\) $ is 8.5, 8.0, 13.5 and 13, respectively. It is observed that \(δ\) should be small and optimized for appropriate momentum to maximize the electron energy gain due to a relativistic longitudinal momentum and the variation of the scattering angle of the electron \(θ\) with respect to electron's injection angle \(δ\) in the presence of magnetic field shows a relatively lower scattering is observed with optimized values of injection angle in the presence of magnetic field.